Impact of Interventions with Modified Snake Ladder Games on Cognitive Abilities and Reducing Cognitive Decline in Aging - Puspitosari, Aniek; Nurhidayah, Ninik; Anggit Jiwantoro, Yudha; Puput Dinda Kurniawan, Ganesa (Jurnal Keterapian Fisik, 2024)
Background: Aging is the process by which humans slowly lose the capacity of their tissue to improve. Elderly people experience physical, mental, and social decline as well as a decrease in cognitive function. To maintain cognitive abilities, interventions in the form of cognitive activities are needed. The purpose of this study was to determine the effect of a cognitive game in the form of a modified Indonesian version of the Snakes and Ladders board game on cognitive abilities. Methods: This research is quantitative research with a pre-experimental design with one group pre-post test. The sampling technique used was purposive sampling with a sample size of thirty people. The instrument used was the MoCA-Ina. The cognitive game Modified Snakes & Ladders Indonesian version was carried out in 8 sessions over 18 weeks. Data analysis using paired t-test. Results: The research sample shows that the characteristics of age are dominated by female middle-aged elderly, and the characteristics of the sample with a final elementary school education are 14 people. Paired t-test results Sig. (2-tailed) = 0.000, which means p-value <0.05. It shows that a cognitive game in the form of a modified Indonesian version of the Snakes and Ladders board game has an effect on cognitive abilities. Conclusion: The modified Indonesian version of the Snake Ladder Game is one of the board games used in activity therapy that can be used for cognitive function in the elderly.